Factors Influencing Profit Distribution Management of Sharia Commercial Banks in Indonesia - Rihfenti Ernayani; Robiyanto Robiyanto; Sudjinan Sudjinan (Universitas Hayam Wuruk Perbanas, 2017)
This study aims to determine and obtain empirical evidences regarding the effect of deposits, product asset management, and rate of inflation on profit distribution management at Sharia Commercial Banks in Indonesia during 2012-2014 periods. By using purposive sampling, 10 samples of Sharia Commercial Banks were observed on a quarterly basis, and the 120 panel data were gained. The data were analyzed by employing multiple linear regression. The result shows that Deposits have positive significant effects on Profit Distribution Management. Productive Assets Management has negative significant effects on Profit Distribution Management. Rate of Inflation has negative significant effect on Profit Distribution Management. Deposits, Productive Assets Management, Rate of Inflation simultaneously have significant effects on Profit Distribution Management.